PLANKTON ABUNDANCE BETWEEN DRY AND RAINY SEASON IN TALLO FRESHWATER AND PANGKEP RIVER - Rakhmad Armus; Alfian Noor; Ahyar Ahmad; Muhammad Lukman (Marina Chimica Acta, 2019)
Plankton abundance is influenced by seasons, sea surface currents (SSC), nutrients and surface temperature (SST). Is a marine organism has a function to stabilize the surface temperature of the earth by regulating the concentration of Dimetyl sulfide (DMS) due to exposure to direct sunlight. There is the ability of the ocean to regulate warming and to regulate the distribution of water vapor in the atmosphere which is controlled by sea surface temperature. Sampling using the transeck system in September and January represents the rainy season and the dry season which is closest to the Tallo river estuary and the Pangkep river estuary represents the estuary region, towards the coast of the spermonde (Litoral) islands and far from the coast (offshore) from freshwater sources, but the relationship of nutrient entry into estuary areas by sea surface currents (SSC) is still poorly known. The dominant aspect of phytoplankton is determined by the amount of nutrients flowing (runoff) from land to estuary to spermonde waters